Palliative Care in a Death-Denying Culture: Exploring Barriers to Timely Palliative Efforts for Heart Failure Patients in the Primary Care Setting. (January 2021) - Crimmins, Rebecca M.; Elliott, Lydia; Absher, Darren T.
Context: Heart failure (HF) is a complex, life-limiting disease that is prevalent and burdensome. All major cardiology societies and international clinical practice guidelines recommend the integration of palliative care (PC) interventions alongside usual HF management. Objectives: The purpose of this review of the literature was to evaluate the various barriers to the early initiation of PC for HF patients in the primary care setting. Methods: An integrative literature review was conducted in order to assess and incorporate the diverse sources of literature available. An EBSCO search identified relevant articles in the following databases: Medline complete, Academic Search Premier, CINAHL, PsycINFO, Cochrane Library, and SocINDEX. The search was limited to full text, peer reviewed, English only, and published between 2010 and 2019. Results: Barriers to the integration of PC for HF patients include poor communication between provider/patient and interdisciplinary providers, the misperception and miseducation of what PC is and how it can be incorporated into patient care, the unpredictable disease trajectory of HF, and the limited time allowed for patient care in the primary care setting. Conclusion: The results of this review highlight a lack of communication, time, and knowledge as barriers to delivering PC. Primary care providers caring for patients with HF need to establish an Annual Heart Failure Review to meticulously evaluate symptoms and allow the time for communication involving prognosis, utilize a PC referral screening tool such as the Needs Assessment Tool: Progressive Disease-Heart Failure, and thoroughly understand the benefits and appropriate integration of PC.